Application of Stad (Student Team Achievement Division) Method in the American Revolution Material Using History Pop-Up Book - Agatha Cristhy Leatemia*; Hotmalina Sihotang (Riwayat: Educational Journal of History and Humanities, 2023)
This research was conducted to determine the improvement of student learning outcomes on the American Revolution subject in the 11th-grade Social Studies class at Citra Berkat Citra Indah High School, Bogor. This study employed the STAD (Student Team Achievement Division) cooperative learning model aided by a History Pop-Up Book for the American Revolution material. The research method used was classroom action research. Data collection was done through observation, tests, and questionnaires. Data analysis technique used descriptive analysis. The sample consisted of 28 students. The initial test results of the 11th-grade Social Studies students were 18%, hence the Cycle I of classroom action research was conducted. The research results indicated that the mastery level in Cycle I was 89.29%, and it increased to 100% in Cycle II. The research findings suggest that there was an improvement in student learning outcomes after implementing the cooperative learning model, STAD, aided by the History Pop-Up Book. In conclusion, the STAD cooperative learning model can be an alternative to enhance student learning outcomes.